PEMANFAATAN LIMBAH KULIT PISANG KEPOK DAN KULIT KAKAO DALAM PEMBUATAN PLASTIK BIODEGRADABLE - Muhammad Erlangga; Vonny Setiaries Johan; Yossie Kharisma Dewi (Fakultas Pertanian Universitas Riau, 2024)
Biodegradable plastic is a polymer generated from renewable materials. One method of manufacture includes use starch derived from organic waste products, such as banana peels. This research sought to establish the ideal ratio of kepok banana peel starch to cocoa pod husk cellulose for the production of biodegradable plastic that complies with the SNI 7818:2014 standard. The study was executed experimentally employing a Completely Randomised Design (CRD), comprising four treatments with starch-to-cellulose ratios of 10:0, 9:1, 8:2, and 7:3, each replicated four times, yielding a total of 16 experimental units. Statistical analysis was conducted using analysis of variance (ANOVA), and significant findings were then examined using Duncan’s Multiple Range Test (DMRT) at a 5% significance threshold. The findings indicated that altering the ratios of kepok banana peel starch and cocoa pod husk cellulose markedly influenced the characteristics of the biodegradable plastic, including water absorption, water vapour transfer rate, tensile strength, elongation, and biodegradation rate. The optimal ratio was achieved with the 7:3 (starch:cellulose) treatment, demonstrating a tensilestrength of 27.72 MPa, elongation of 1.5%, water absorption of 28.96%, water vapour transfer rate of 0.228 g/m2/hour, and a biodegradation duration of 12 days.